Sustainable development of an Ultra-High Performance Fibber Reinforced Concrete (UHPFRC): towards partial replacement of cement by slags - Pérez-García, Francisca; Rubio Cintas, María Dolores; Oliveira, Miguel José; Silva, Elisa María; Parrón-Rubio, María Eugenia; Fernández Ruiz, Manuel Alejandro (My University, 2019)
The global production of concrete represents, every year, more than 5% of the anthropogenic emissions of carbon dioxide, mainly from the production of cement. This negative factor can be improved by incorporating supplementary cementitious materials in order to replace cement. In the last few decades, research has been conducted on what it is known as Ultra High Performance Fibber Reinforced Concrete (UHPFRC). The term includes a broad range of materials such as defect-free, dense particle, engineered composite, multi-scale particle and fibber-reinforced cementitious materials, with enhanced properties. UHPFRC has better mechanical and durability properties compared to normal strength concrete. Other benefits of using UHPFRC on a structure includes the reduction of concrete sections, concrete formwork, labour, equipment and time of construction. Despite of the benefits associated to this material, the UHPFRC is still struggling to be universally applied, mainly due to its high cost and its high environmental impact. UHPFRC cost is higher than normal concrete, due to a very high powder content and steel ﬁbber addition. However, the production of UHPFRC using locally available materials, under normal curing conditions, should reduce its cost and turned it into a more attractive construction product. In this paper, the fresh and hardened properties of a specific UHPFRC composition are presented. The mixture replaces a significant percentage of cement by slags, and the results reveal the viability of the proposed mix. The environmental performance of the mixture confirmed the improvement on the material sustainability and allowed the identification of some potential future studies.
Keywords: Hormigón armado con fibras; Hormigón de alta resistencia; Cemento; Hormigón